Delayed Functional Independence After Neurothrombectomy (DEFIANT) score: analysis of the Trevo Retriever Registry - Jadhav, Ashutosh P; Desai, Shashvat M; Gupta, Rishi; Baxter, Blaise W; Bartolini, Bruno; Krajina, Antonin; English, Joey D; Nogueira, Raul G; Liebeskind, David S; Veznedaroglu, Erol; Budzik, Ronald F (Journal of neurointerventional surgery, 2023)
BACKGROUND: Chronological heterogeneity in neurological improvement after endovascular thrombectomy (EVT) for large vessel occlusion (LVO) stroke is commonly observed in clinical practice. Understanding the temporal progression of functional independence after EVT, especially delayed functional independence in patients who do not improve early, is essential for prognostication and rehabilitation. We aim to determine the incidence of early functional independence (EFI) and delayed functional independence (DFI), identify associated predictors after EVT, and develop the Delayed Functional Independence After Neurothrombectomy (DEFIANT) score. METHODS: Demographic, clinical, radiological, treatment, and procedural information were analyzed from the Trevo Registry (patients undergoing EVT due to anterior LVO using the Trevo stent retriever). Incidence and predictors of EFI (modified Rankin Scale (mRS) score 0-2 at discharge) and DFI (mRS score 0-2 at 90 days in non-EFI patients) were analyzed. RESULTS: A total of 1623 patients met study criteria. EFI was observed in 45% (730) of patients. Among surviving non-EFI patients (884), DFI was observed in 35% (308). Younger age (p=0.003), lower discharge National Institutes of Health Stroke Scale (NIHSS) score (p<0.0001), and absence of any hemorrhage (p=0.021) were independent predictors of DFI. After age 60, the probability of DFI declines significantly with 5 year age increments (approximately 7% decline for every 5 years; p(DFI)= 1.3559-0.0699, p for slope=0.001). The DEFIANT score is available online (https://bit.ly/3KZRVq5). CONCLUSION: Approximately 45% of patients experience EFI. About one-third of non-early improvers experience DFI. Younger age, lower discharge NIHSS score, and absence of any hemorrhage were independent predictors of DFI among non-early improvers.
Keywords: cévní mozková příhoda; trombektomie; předškolní dítě; Humans; Functional Status; lidé středního věku; Middle Aged; ischemická cévní mozková příhoda; Registries; Brain Ischemia; Ischemic Stroke; Stroke; Child, Preschool; funkční status; Endovascular Procedures; endovaskulární výkony; výsledek terapie; Treatment Outcome; ischemie mozku; registrace; lidé; Thrombectomy